2023
DOI: 10.1002/sstr.202200338
|View full text |Cite
|
Sign up to set email alerts
|

Functional Layers of Inverted Flexible Perovskite Solar Cells and Effective Technologies for Device Commercialization

Abstract: Perovskite solar cells (PSCs) have emerged as a rising star in photovoltaic fields in recent years due to their very impressive properties such as ease of fabrication, low cost, and high-power conversion efficiency (PCE). [1][2][3][4][5][6][7][8][9][10][11] Over the past decade, the PCEs of PSCs have dramatically increased to certified record values of 25.7% and 25.37% for single-junction regular n-i-p and inverted p-i-n PSCs, respectively, owing to excellent properties of perovskite such as high light absorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 241 publications
(632 reference statements)
0
18
0
Order By: Relevance
“…Herein, the thermal activation (or exciton bonding) energy can be utilized to evaluate the barrier between free-exciton (FE) and self-trapped exciton (STE). The exciton bonding energy (E a ) can be determined by the temperature-dependent emission intensity based on the Arrhenius-type formula: (3) in which I PL and I 0 are the emission intensities at different temperatures (T) and 0 K, respectively, and k B is the Boltzmann constant. 49 As depicted in Figure 3e, the calculated E a of 89.85 meV is far larger than the thermal energy (26 meV) of FE at room temperature and those of 3D perovskites.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herein, the thermal activation (or exciton bonding) energy can be utilized to evaluate the barrier between free-exciton (FE) and self-trapped exciton (STE). The exciton bonding energy (E a ) can be determined by the temperature-dependent emission intensity based on the Arrhenius-type formula: (3) in which I PL and I 0 are the emission intensities at different temperatures (T) and 0 K, respectively, and k B is the Boltzmann constant. 49 As depicted in Figure 3e, the calculated E a of 89.85 meV is far larger than the thermal energy (26 meV) of FE at room temperature and those of 3D perovskites.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In the past several decades, metal halide perovskites have emerged as one new kind of most promising optoelectronic material with wide applications in solid-state luminescence, light emitting diodes (LEDs), photovoltaic solar cells, photodetectors, lasers, scintillators, and so on. − In particular, three-dimensional (3D) all-inorganic lead perovskite nanocrystals (PNCs) of CsPbX 3 (X = Cl, Br, I) are capable of displaying outstanding photoluminescence (PL) performance with multiple advantages of adjustable bandgap and emission wavelength in the whole visible spectral range, narrow emission linewidth, superhigh photoluminescence quantum yield (PLQY), color purity, etc. − Simultaneously, 3D PNCs are also regarded as preferred candidates of LEDs in full-color display applications with ever-increasing external quantum efficiency (>20%). − Since 2018, 3D PNCs were found to be new-generation scintillators with strong X-ray absorption ability and intense radioluminescence (RL) in an adjustable visible light range . As a scintillator, 3D PNCs can downconvert higher-energy X-rays to ultraviolet–visible-infrared light, and the assembled film can be explored as flexible, stable, and high-performance X-ray scintillators, which showcase wide advanced applications in radiation monitoring, nondestructive or noncontact inspection, medical imaging, space exploration, other associated nuclear radiation industries, etc. − Despite the multiple advanced optoelectronic performance of 3D PNCs, some inescapable drawbacks remain to extremely restrict the application values, such as high toxicity of Pb 2+ , low light yield (∌21,000 photons/MeV), serious aggregation caused quenching (ACQ)-induced luminescence attenuation or quenching, limited structural adjustability, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the potential applications of CQDs in perovskite solar cells are expected. 49,50 Authors' contributions R. K.: formal analysis, investigation, methodology, and writing -original draft; K. S.: investigation and methodology; A. O.: investigation; K. T.: investigation; Y. I.: supervision and writing -review and editing; T. I.: conceptualization, funding acquisition, project administration, supervision, and writing -review and editing. All authors gave final approval for publication and agreed to be held accountable for the work performed therein.…”
Section: Discussionmentioning
confidence: 99%
“…As a universal polyester engineering polymer, polyethylene terephthalate (PET) possesses a few characteristics such as excellent mechanical properties, biocompatibility, electromagnetic performance, 1–3 and extreme‐temperature resistance. It is reported that an innovative material‐copolymer of poly(ethylene‐terephthalate) was prepared and the related detection showed that no cytotoxicity was observed and no significant decrease of cells density as well as no cells growth reduction was noticed 4 .…”
Section: Introductionmentioning
confidence: 99%